The bees - Paull, Laline (2014)
"A member of the lowest caste in her orchard hive, Flora 717, due to her courage and strength, finds her way into the Queen's inner sanctum where she discovers secrets about the hive that cause her to challenge authority and perform unthinkable acts"-- publisher's website.
Keywords: Bees -- Fiction; Queens -- Fiction; Survival -- Fiction; Fertility -- Fiction; Abnormalities, Human -- Fiction; Government, Resistance to -- Fiction; Fiction; Dystopias; Suspense fiction